Pengembangan Media Pembelajaran Matematika Berbasis Macromedia Flash Materi Luas dan Keliling untuk Meningkatkan Motivasi Belajar Siswa - Krisma Widi Wardani; Danang Setyadi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
One of the computer-based mathematics learning media developed is Macromedia Flash-based learning media. Macromedia Flash-based learning media that have been available so far have not been students to be actively involved in using the media. This has encouraged researchers to develop new Macromedia Flash-based media. This research is development research. The development model used in 4D, namely Defines, Design, Develop and Disseminate. The subjects consisted of 60 students in grade 4 at SD Mardirahayu 01 and 02 Ungaran. The research instrument consisted of media validation sheets, material validation sheets, student response sheets, and motivation questionnaires. Research data were analyzed qualitatively and quantitatively. The results showed that the media developed were valid and could increase students' motivation in learning mathematics in a broad and mobile material.